A review of prognostic molecular biomarkers for glioblastoma and their clinical significance for diagnosis and treatment - A.M. Netliukh; T.А. Malysheva; A.V. Zanevych; N.O. Fesh; Yu.V. Flys; A.A. Sukhanov (Українська Інтервенційна Нейрорадіологія та Хірургія)
Glioblastoma (GBM) is a WHO grade IV malignant brain tumor with a poor prognosis, and it is the most common primary malignant brain tumor in adults. The estimated overall survival rate for patients with GBM is less than 1.5 years, with a 5-year survival rate of about 5 %. Current treatment standards include maximal (Gross total) resection, which is rarely achieved due to the diffuse-invasive nature of these tumors, and radiotherapy with concomitant chemotherapy, such as temozolomide. New technologies, including genetic research and advanced statistical methods, enhance therapeutic approaches and create new treatment opportunities. Certain genes are crucial for understanding tumorigenesis and tumor prognosis, with each GBM subtype associated with specific genetic and epigenetic changes. Our goal was to conduct an up-to-date review of common molecular markers, namely isocitrate dehydrogenase 1 and 2 (IDH1/2), O-6-methylguanine-DNA methyltransferase (MGMT), p53 protein, epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor (PDGFR), 1p/19q codeletion, telomerase reverse transcriptase (TERT), circulating tumor cells, and microRNAs. Established biomarkers are widely used in clinical neuro-oncology practice and play a critical role in improving diagnostics, determining prognosis, and predicting treatment responses. The roles of biomarkers such as MGMT and IDH1/2 are well-established. Many studies indicate better outcomes from surgical and radiation treatments in patients with mutations in these genes. We also highlighted potential biomarkers, especially easily accessible circulating blood markers, which require thorough future evaluation for their prognostic and/or predictive utility for GBM in therapeutic settings. However, research on other biomarkers, such as the p53 protein, EGFR, PDGFR, 1p/19q codeletion, the alpha-thalassemia mental retardation X-linked syndrome protein (ATRX), TERT, loss of heterozygosity of chromosome 10, circulating tumor complexes, and microRNAs, remains promising. Overall, identifying specific biomarkers enables the selection of effective treatments and improves the prognosis for patients with malignant gliomas.